2014
DOI: 10.1093/bioinformatics/btu156
|View full text |Cite
|
Sign up to set email alerts
|

Basin Hopping Graph: a computational framework to characterize RNA folding landscapes

Abstract: The algorithms described here are implemented in C++ as standalone programs. Its source code and supplemental material can be freely downloaded from http://www.tbi.univie.ac.at/bhg.html.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 49 publications
1
50
0
Order By: Relevance
“…Understanding the kinetics, such as the rate and pathways for the conformational changes, is critical for deciphering the mechanism of RNA function (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Extensive experimental and theoretical studies on RNA folding kinetics have provided significant insights into the kinetic mechanism of RNA functions (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). However, due to the complexity of the RNA folding energy landscape (37)(38)(39)(40)(41)(42)(43)(44)(45)(46) and the limitations of experimental tools (47)(48)(49)(50)(51)(52)(53)(54)(55), many fundamental problems, ...…”
mentioning
confidence: 99%
“…Understanding the kinetics, such as the rate and pathways for the conformational changes, is critical for deciphering the mechanism of RNA function (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Extensive experimental and theoretical studies on RNA folding kinetics have provided significant insights into the kinetic mechanism of RNA functions (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). However, due to the complexity of the RNA folding energy landscape (37)(38)(39)(40)(41)(42)(43)(44)(45)(46) and the limitations of experimental tools (47)(48)(49)(50)(51)(52)(53)(54)(55), many fundamental problems, ...…”
mentioning
confidence: 99%
“…available within the global flooding barriers pipeline, is to ignore RNA structures above a global upper absolute energy bound (maxE), also discussed e.g. in (Hofacker et al, 2010;Kucharík et al, 2014). Due to the bellshaped density-of-states distribution of RNAs (see e.g.…”
Section: Maxe -Global Absolute Energy Boundmentioning
confidence: 99%
“…Entzian & Raden local minima and subsequently estimates the minimal energy barrier between them via direct folding pathway computations (Kucharík et al, 2014). While this enables kinetics predictions for longer RNAs, the procedure might miss transition states (Kucharík et al, 2014) and the dynamics can be distorted due to poor transition rate estimates based on saddle heights only (see supplementary material F).…”
mentioning
confidence: 99%
“…Since barriers relies on an exhaustive enumeration of low energy structures, the computational effort grows exponentially with sequence size, which limits the length of RNAs that can be studied to a little over 100 nt. Recently, a number of heuristic approaches have been reported that attempt to raise this limit based on flooding techniques [34,24] or sampling of local minima [27,28,20,21].…”
Section: The Barriers Approachmentioning
confidence: 99%